Principio de equidad procesal - Peñaranda Quintero, Héctor Ramón (Nómadas. Critical Journal of Social and Juridical Science, 2009)
As far as the fairness principle one does not treat but of the justice of the tactical mission, the judge before the law is going to fail by the feeling of having or of she brings back to consciousness, rather that by the final text of the law, is natural justice by opposition exactly of the positive law. It authorizes the judge to decide according to the good fairness in two situations defined by the law: 1. - When the parts in common agreement therefore they ask for and 2. - When one is rights available.